Agromyces chromiiresistens sp. nov., Novosphingobium album sp. nov., Sphingobium arseniciresistens sp. nov., Sphingomonas pollutisoli sp. nov., and Salinibacterium metalliresistens sp. nov.: five new members of Microbacteriaceae and Sphingomonadaceae from polluted soil - Liu, Ze-Shen; Wang, Ke-Huan; Cai, Man; Yang, Mei-Ling; Wang, Xiao-Kang; Ma, Hong-Lin; Yuan, Yi-Han; Wu, Lin-Huan; Li, De-Feng; Liu, Shuang-Jiang (Frontiers in Microbiology, 2023)
There are many unidentified microbes in polluted soil needing to be explored and nominated to benefit the study of microbial ecology. In this study, a taxonomic research was carried out on five bacterial strains which were isolated and cultivated from polycyclic aromatic hydrocarbons, and heavy metals polluted soil of an abandoned coking plant. Phylogenetical analysis showed that they belonged to the phyla Proteobacteria and Actinobacteria, and their 16S rRNA gene sequence identities were lower than 98.5% to any known and validly nominated bacterial species, suggesting that they were potentially representing new species. Using polyphasic taxonomic approaches, the five strains were classified as new species of the families Microbacteriaceae and Sphingomonadaceae. Genome sizes of the five strains ranged from 3.07 to 6.60 Mb, with overall DNA G+C contents of 63.57–71.22 mol%. The five strains had average nucleotide identity of 72.38–87.38% and digital DNA-DNA hybridization of 14.0–34.2% comparing with their closely related type strains, which were all below the thresholds for species delineation, supporting these five strains as novel species. Based on the phylogenetic, phylogenomic, and phenotypic characterizations, the five novel species are proposed as Agromyces chromiiresistens (type strain H3Y2-19aT = CGMCC 1.61332T), Salinibacterium metalliresistens (type strain H3M29-4T = CGMCC 1.61335T), Novosphingobium album (type strain H3SJ31-1T = CGMCC 1.61329T), Sphingomonas pollutisoli (type strain H39-1-10T = CGMCC 1.61325T), and Sphingobium arseniciresistens (type strain H39-3-25T = CGMCC 1.61326T). Comparative genome analysis revealed that the species of the family Sphingomonadaceae represented by H39-1-10T, H39-3-25T, and H3SJ31-1T possessed more functional protein-coding genes for the degradation of aromatic pollutants than the species of the family Microbacteriaceae represented by H3Y2-19aT and H3M29-4T. Furthermore, their capacities of resisting heavy metals and metabolizing aromatic compounds were investigated. The results indicated that strains H3Y2-19aT and H39-3-25T were robustly resistant to chromate (VI) and/or arsenite (III). Strains H39-1-10T and H39-3-25T grew on aromatic compounds, including naphthalene, as carbon sources even in the presence of chromate (VI) and arsenite (III). These features reflected their adaptation to the polluted soil environment.